The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1097/00002060-200009000-00012
|View full text |Cite
|
Sign up to set email alerts
|

One Program’s Experience of OSCE vs. Written Board Certification Results

Abstract: The objective structured clinical examination (OSCE) has been the focus of a lot debate with respect to reliability and validity. Much of the controversy surrounding these components lies in a lack of comparison with a "gold standard." Further work is needed to improve the evaluation of clinical skills to the point that a gold standard can truly be said to exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The psychometric properties of performance‐based assessment have been the subject of considerable debate in the medical education literature 26–28 . Several factors in the construction of objective structured examinations may help ensure the validity of these tests.…”
Section: Discussionmentioning
confidence: 99%
“…The psychometric properties of performance‐based assessment have been the subject of considerable debate in the medical education literature 26–28 . Several factors in the construction of objective structured examinations may help ensure the validity of these tests.…”
Section: Discussionmentioning
confidence: 99%
“…Although a well-constructed and implemented OSCE is a valid and reliable method of evaluating clinical competence, 4,[7][8][9] there is overwhelming evidence from the literature to support that it is not without limitations. 10 Furthermore, our hybrid OSCE had some peculiar elements that needed to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Experiences in other health professions have established the reliability and validity of a well-constructed and implemented OSCE. [8][9][10] The use of OSCEs in high-stakes settings (such as certification examinations and maintenance of competency reviews) has demonstrated their value in assessing clinical competency. For example, the Medical Council of Canada has used an OSCE in its entry-topractice examinations since 1994.…”
Section: Introductionmentioning
confidence: 99%